THE ANALYSIS OF PARTIAL DISCHARGE (PD) FROM ELECTRICAL TREEING IN LINEAR LOW DENSITY POLYETHYLENE (LLDPE) AND HIGH DENSITY POLYETHYLENE (HDPE) - Hermawan Hermawan; Abdul Syakur (Diponegoro University, 2008)
Recently, the transmission of electric energy has been developed by insulated cable. The suitable materialas an insulated cable is LLDPE and HDPE. In order to understand the quality of insulation system, themeasuring of PD has done. PD could begin completely insulation failure (breakdown). Therefore, it is veryimportant to understand the characteristic of PD and the enclose event on it, because PD is a main factorwhich caused insulation failure.This paper presents the result of PD measurement in the laboratory that used needle-plane electrode. Itwas supported by equipments such as osiloskop Digital GDS 2104 GW Instek, HPF, and RC detector.Polymer sample that used in this research is LLDPE (Linier Low Density Polyethylene) and HDPE with 20x 4 x 25 mm3 dimension in each. Needle was made by steel (length 50 mm and diameter 1.15 mm), it wasstick to the polymer material. The distance between needle to the plane is 5 mm. The applied voltage foreach sample was 16 kVrms, 18 kVrms, 20 kVrms and 22 kVrms. The Taking of PD data was done in thefirst minute, 10th minute, 20th and so on until 180th minute.The measurement result shows that the characteristic of PD number and maximum charge as a function oftime and as a function of applied voltage inclined increasing both on LLDPE and HDPE. But, PD intensityin HDPE is higher than LLDPE.